Role of Membrane Biophysics in Alzheimer's - related cell pathways - Zhu, Donghui; Bungart, Brittani L.; Yang, Xiaoguang; Zhumadilov, Zhaxybay; Lee, James C.; Askarova, Sholpan (Frontiers in Neuroscience, 2015)
Cellular membrane alterations are commonly observed in many diseases, including Alzheimer’s disease (AD). Membrane biophysical properties, such as membrane molecular order, membrane fluidity, organization of lipid rafts, and adhesion between membrane and cytoskeleton, play an important role in various cellular activities and functions. While membrane biophysics impacts a broad range of cellular pathways, this review addresses the role of membrane biophysics in amyloid-β peptide aggregation, Aβ-induced oxidative pathways, amyloid precursor protein processing, and cerebral endothelial functions in AD. Understanding the mechanism(s) underlying the effects of cell membrane properties on cellular processes should shed light on the development of new preventive and therapeutic strategies for this devastating disease.